Cardiac adaptation to chronic high-altitude hypoxia: beneficial and adverse effects - Ostadal, B; Kolar, F (Respiratory physiology & neurobiology, 2007)
This review deals with the capability of the heart to adapt to chronic hypoxia in animals exposed to either natural or simulated high altitude. From the broad spectrum of related issues, we focused on the development and reversibility of both beneficial and adverse adaptive myocardial changes. Particular attention was paid to cardioprotective effects of adaptation to chronic high-altitude hypoxia and their molecular mechanisms. Moreover, interspecies and age differences in the cardiac sensitivity to hypoxia-induced effects in various experimental models were emphasized.
Keywords: hypoxie; Hypoxia; Chronic Disease; aklimatizace; chronická nemoc; Ischemia; Myocardial Reperfusion Injury; Acclimatization; ischemie; věkové faktory; reperfuzní poškození myokardu; kyslík; myokard; zvířata; Altitude; Myocardium; atmosférický tlak; Age Factors; Atmospheric Pressure; nadmořská výška; Oxygen; Animals